2021
DOI: 10.3389/fpsyg.2021.631979
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Daydreaming in an Adult Italian Population During the COVID-19 Lockdown

Abstract: During the COVID-19 outbreak, individuals with or without mental disorders may resort to dysfunctional psychological strategies that could trigger or heighten their emotional distress. The current study aims to explore the links between maladaptive daydreaming (MD, i.e., a compulsive fantasy activity associated with distress and psychological impairment), psychological symptoms of depression, anxiety, and negative stress, and COVID-19-related variables, such as changes in face-to-face and online relationships,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
5
27
0
Order By: Relevance
“…Younger people reported a greater presence of daydreams. This finding is in line with the literature [ 52 , 53 ] and with the evidence that young people are increasingly aware of the phenomenon of maladaptive daydreaming. Given that it is often a self-diagnosed phenomenon, it may be that young people are more likely to notice and report, and willing to share, their experiences of it.…”
Section: Discussionsupporting
confidence: 92%
“…Younger people reported a greater presence of daydreams. This finding is in line with the literature [ 52 , 53 ] and with the evidence that young people are increasingly aware of the phenomenon of maladaptive daydreaming. Given that it is often a self-diagnosed phenomenon, it may be that young people are more likely to notice and report, and willing to share, their experiences of it.…”
Section: Discussionsupporting
confidence: 92%
“…This work is part of a larger multicentre research project, coordinated by the University of Parma, entitled 'Resilience during the time of COVID-19: how to react to perceived stress?'. The project was started in March 2020 during the first wave of the COVID-19 pandemic in Italy and aims to investigate, through a prospective design with a 6-month follow-up, the ways in which people cope with stress related to lockdown and the immediate and longterm effects on sleep quality, psychological distress, resilience, and dream activity (such as daydreaming and night dreaming) (for more details please refer Franceschini et al, 2020;Lenzo et al, 2020;Scarpelli et al, 2021;Musetti et al, 2021). The research project was conducted in accordance with the Declaration of Helsinki and the study protocol was approved by the Ethics Committee of the University of Messina.…”
Section: Methodsmentioning
confidence: 99%
“…During the most critical phase of the pandemic, people who experienced anxiety and depression are more likely to be absorbed in an inner fantasy world, which in turn may increase their emotional distress. 8 Nonetheless, these were not the only forms of psychological symptoms Italian people experienced. A study involving a large sample of subjects has found that more than half of them reported poor sleep quality including sleep disturbance, awakening with shortness of breath or with headache, sleep inadequacy, and somnolence.…”
Section: Introductionmentioning
confidence: 99%